Motivations, challenges and coping strategies of UP students working as call center agents - Lorenzana, Karen Ruth C.
ABSTRACT Increase in the number of UP students working in the call center business garnered the researchers? interest. Thus, the researchers would like to find out the motivations, challenges, and coping strategies these students have in choosing to study while working. The researchers went to 4 sites to gather 53 answered questionnaires, and purposive sampling was employed ? excluding people who do not fit the profile of being undergraduate degree enrollees during the Academic Year 2009-2010 in UP, single, and at least 18 years old. The form has three major sections, all sections being checklists for (1) motivations, (2) challenges, and (3) coping strategies in being working students. The results were tabulated and plotted in Frequency Distribution Tables. Results show that UP students are highly motivated to work as call center agents for the financial benefits, easy application process, and the job is not mentally draining. Challenges include excessive tardiness and absences from school, difficulties meeting school requirements, and passive class participation. Coping strategies include studying during days off, decreasing time for leisure activities, and using uploaded materials as reference to the lessons missed. Developing vices such as smoking and drinking has outnumbered those who chose not to engage in these activities. Developing working student-friendly policies in UP, Call Centers and Government programs, as well as having family support systems, are recommended to help the increasing number of working students better manage their work and academic responsibilities.